ТРУДНОЩІ ХУДОЖНЬОГО ПЕРЕКЛАДУ: ПЕРЕКЛАДАЦЬКІ СТРАТЕГІЇ ТА РІШЕННЯ (на матеріалі перекладу твору Harlan Coben “The Match”) - Бялик, Василь Дмитрович; Юрій, Мельничук; Сорочан, Олександр (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Германська філологія, 2024)
This article explores the intricacies of literary translation and the strategies utilized in translating the lexical content of Harlan Coben's novel "The Match" into Ukrainian. The focus is primarily on phonetic, lexical-grammatical, and lexical-semantic aspects of the translation process. The study aims to uncover the techniques and transformations translators employ to reproduce the English text in Ukrainian while ensuring adequacy and fidelity to the source material. The research uses the exhaustive selection of lexical units to analyze translation transformations, alongside a review of scholarlytranslation and the various approaches to perspectives on the complexities of literary transferring text from one language to another.Descriptive methods and analysis of translationtransformations were applied to study Harlan Coben's unique idiolect in detail. The results revealed that at the lexical level, transcription (61%) and transliteration (39%) were the predominant techniques for rendering proper names. In the lexical-semantic domain, modulation (73%) and differentiation (27%) were found to be the most commonly used methods, whereas in the lexical-grammatical area, transposition (93%) was the leading strategy. The study suggests that the most frequently employed translation methods in the examined Ukrainian translation of "The Match" are transcription, modulation, and transposition. The article provides translation variants for lexical units from the novel to ensure maximum adequacy in conveying the original content within the target language's cultural and linguistic framework.By expanding on the content of the article, the research offers a deeper understanding of the translation process, the challenges translators face, and the strategies they use to render a literary work from English to Ukrainian. It underscores the importance of maintaining fidelity to the original text while ensuring that the translation aligns with the linguistic and cultural context of the target audience.
Keywords: literary text, translation adequacy, translation transformations, lexical units, language levels, context.